2014
DOI: 10.1097/nna.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Older RNs Keep Working?

Abstract: Retaining older nurses in the workforce is an important strategy for managing workforce shortages. Nurse executives will need to consider strategies that will enhance retention of older nurses and focus on the reasons older nurses want to keep working.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 18 publications
5
36
0
Order By: Relevance
“…The costs of such programmes for the prevention and treatment of hypertension in nurses are likely to be far outweighed by the benefits in workforce productivity (Asay et al., ). While many of the factors related to health are personal (Graham, Donoghue, Duffield, & Griffiths, ), nurse managers are in a position to recommend that their staff protect their good health, engage in regular screening and accommodate health changes in staff when they occur. Health promotion units for staff have become commonplace in workplaces and are involved in screening campaigns, which could be promoted by nurse managers to their staff (Ogunmoroti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The costs of such programmes for the prevention and treatment of hypertension in nurses are likely to be far outweighed by the benefits in workforce productivity (Asay et al., ). While many of the factors related to health are personal (Graham, Donoghue, Duffield, & Griffiths, ), nurse managers are in a position to recommend that their staff protect their good health, engage in regular screening and accommodate health changes in staff when they occur. Health promotion units for staff have become commonplace in workplaces and are involved in screening campaigns, which could be promoted by nurse managers to their staff (Ogunmoroti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, with a randomly selected sample of 319 registered nurses in Australia (mean age 55), Duffield et al () found that 17% of the respondents noted overall health was a factor in their intent to retire early; overall health was described as age related, or related to fatigue/burnout. On a positive note, reasons to stay in the workplace cited by nurses 50 years and older include the opportunity to participate in decision‐making related to work activities (Hellemans & Closon, ), and in a study with nurses 45 years and older, good working relationships and interesting work (Graham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom and Canada, 20% and 33%, respectively, of the nurse population are aged over 50 years (Keller & Burns, ). In Australia, the average age of nurses was 44.5 years in 2011; nurses aged 50–54 years accounted for the largest proportion (Graham et al., ). In New Zealand, approximately 40% of the nurses were aged over 50 years (Clendon & Walker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (Auerbach, Buerhaus, & Staiger, ; Bishop, ; Duffield et al., ; Graham et al., ; Meng, ; Nooney et al., ; Spiva, Hart, & McVay, ; Stichler, ; Valencia & Raingruber, ; Williamson et al., ) found that the main factors that influence whether older nurses plan to remain in clinical practice are the working conditions; personal health and economic status; and other factors such as working hours, workload, social welfare and personal circumstances. Meng () showed that the main factors that affect retirement planning by older nurses are health status, economic status, attitude toward retirement and satisfaction with current work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation